Art collections and taste in the Spanish Siglo de Oro - Federico Etro; Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
We analyze art pricing in a unique dataset on Madrid inventories between 1600 and 1750. Hedonic regressions reveal a number of interesting facts about the taste of Baroque Spanish collectors and the imports of foreign paintings. The hedonic price index shows an impressive increase in the price of paintings (relative to the cost of living) during the XVII century, in line with the Lopez hypothesis for which investment in art increases in wealthy societies without new productive investment opportunities. We examine price differentials between domestic and imported paintings: at the beginning of the century local works were priced substantially below imported paintings, but the price gap is gradually reduced during the century, with an increasing contribution of the younger painters. This is in line with a Schumpeterian hypothesis for which increasing demand induced increasing domestic quality, as priced by the market, and created the conditions for what is known as the Siglo de Oro of Spanish art.
Keywords: Z11; N0; L14; D4; 330; Hedonic price index; Lopez hypothesis; Schumpeterian hypothesis